Your face looks the same as before, only prettier: The facial skin homogeneity effects on face change detection and facial attractiveness perception - Sun, Yu-Hao P.; Zhang, Xiaohui; Lu, Ningyan; Li, Jing; Wang, Zhe (Frontiers in Psychology, 2022)
Previous studies suggested that (1) facial attractiveness perception can be increased with facial skin homogeneity improving; and (2) human’s facial change detection increases along with facial skin homogeneity increases. However, it’s unknown whether a face can be perceived prettier than it did before while still being considered as physically the same. It possible that these two kinds of cognitive-aesthetic processing may have separate mathematical functions in psychophysical studies. In other words, human’s facial attractiveness differentiation may be more sensitive than facial change detection. In this current study, we explored above questions. Using three types of psychophysical techniques to manipulate facial skin homogeneity, we measured how participants’ sensitivity to facial skin homogeneity and attractiveness change. Results showed a linear function curve for facial physical change detection and a logarithmic function curve was drawn in the forced-choice technique, which was the most sensitive one, indicating that participants can judge a face prettier than before without being aware of it has physically changed. Besides, two linear function curves were shown in a same/different technique and a rating technique. Taken together, this current study revealed that facial attractiveness can be enhanced and discriminated by improving facial skin homogeneity, without being realized by people with conscious awareness that the face has been changed.